Análisis, diseño y simulación multifísica de una antena Fotoconductora Terahertz usando el método de elementos finitos - Gonzalez Galindo, Diana; Torres Urrea, Cristhian; Corredor Camargo, Oscar Fabian; Suarez Mora, David; Criollo Paredes, Carlos (Ingeniería, 2020)
Context: The study of nanotechnology has shown great advances, which include research and exploration of the TeraHertz (THz) region, where one of the most common approaches is the use of photoconductive antennas (PCA) due to the intrinsic properties of their emission the non-destructive nature of this type of radiation. Method: This paper describes the concept of antenna its radiation principles, the mathematical foundations, the material used for radiation, and the adjustment of the parameters to find a result of the pulse in THz by using the finite element method, accessible in the COMSOL Multiphysics software. Results: The result of a computational modeling is presented, which studies the behavior of a PCA, where the input of the chosen model corresponds to the geometry and material of the antenna, thus showing the concentration of the electric field in the GAP zone of the dipole and the substrate of the semiconductor. Conclusions: Given the theoretical foundations that describe the behavior of PCAs in THz, it was possible to configure parameters such as the geometry of the antenna, the laser to be used, and the construction materials to achieve the generation of a photocurrent peak in the order of 0,1-1,2 THz.